The Difference of Potassium Level in Stage 5 Kidney Chronic Disease Patients Whose Using New and Re-use Hemodialyzer in RSD dr. Soebandi Jember - Yuli Hermansyah; Dinda Ayu Wanodya Supriatiningsih; Bagus Hermansyah (Journal of Agromedicine and Medical Sciences, 2019)
Stage 5 chronic kidney disease (CKD) is a condition where the renal function decrease, marked by the GFR value < 15/ml/minute/1,73 m2 with or without kidney damage history for 3 months or more that needs kidney replacement therapy, including hemodialysis. In Indonesia, hemodialysis was chosen for 82% from all the cases that needs kidney replacement therapy. However, the cost for hemodialysis therapy is considered as too expensive and burdens The National Health Insurance, Badan Penyelenggara Jaminan Sosial (BPJS), allowing the reuse of hemodialyzer as an alternative for cost-effectiveness. Re-use hemodialyzer is a term for using the same hemodialyzer for the same patient but on different therapy session. The main purpose of this research is to investigate the difference of Potassium level in stage 5 chronic kidney disease patients whose using new and re-use hemodialyzer in RSD dr. Soebandi Jember. This research used quasi experimental design by using blood sample that will be measured for the potassium level after using new hemodialyzer and re-use hemodialyzer for the 4th time in Hemodialysis Installation of RSD dr. Soebandi Jember on December 2018. Total sample of 19 patients chosen using inclusion and exclusion criteria. Collected data were analyzed using paired t-test. The result of statistical test shows that there is no significance potassium level difference in stage 5 chronic kidney disease whose using new and re-use hemodialyzer for the 4th time (p=0,094). The effectivity of hemodialyzer that still has a good condition and hemodialysis therapy that has been done in accordance with the procedure until the 4th reuse is the main factor of this result. Keywords: CKD, potassium, re-use hemodialyzer